Keragaan Pohon Cengkeh Terpilih Tipe Zanzibar dan Siputih Palabuhanratu - Randriani, Enny; Syafaruddin, Syafaruddin (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The demand for good quality of cloves seed continues to grow in accordance with clove revitalization program held by the government. Therefore, it is important to improve the physical and genetic properties of clove seed in order to guarantee its yield potential. The diverse genetic resources of local variety of cloves in Sukabumi, Indonesia has been utilized, through selection breeding program, to select superior trees as seed parents. There are two types of cloves identified, i.e. Zanzibar and Siputih. The former type has been widely cultivated in Buniwangi District and has known as descendant of open pollinated Zanzibar type of cloves ever planted in Cibinong, Indonesia. On the other hand, the later type of cloves has been cultivated in Sukamaju District and has known as descendants of Siputih type growing in Bogor, Indonesia. Selection for superior trees of Zanzibar and Siputih types was based mainly on high productivity (total fresh weight of harvested flower buds). The average productivity of selected superior trees over the past five years (2006-2010) of Zanzibar and Siputih type was reached of 161.8 kg/tree/year and 93.1 Â kg/tree/year, respectively. In addition, the total eugenol content of those d types of cloves was of 88.39% and 81.05%.